O papel do professor de direito na universidade e o desafio de ensinar para a nova geração: o uso da disciplina direito e cinema - Almeida Júnior, Washington Carlos de (2021)
The main theme of this dissertation is to analyze the role of the Law Professor at the University. Education will be addressed at the outset as a fundamental right of a social nature and its relationship with the reality of the new classroom, linked to the principle of gratuity, public quota policies, and affirmative citizenship actions. We will then point out the current challenges in the classroom, presenting the legal issues (LDB, National Education Plan and the National Curriculum Guidelines for the Undergraduate Law Course), and their consequences in the teaching-learning process. Next, we will contextualize the recent scenario of the commercialization of higher education and the impacts on teaching and training of law professors. Therefore, this dissertation aims to investigate teacher training, and to shift the gaze to the needs of current students and to the application in the classroom of Active Learning Methodologies, as well as to propose alternatives for this context, presenting new, necessary and unusual ones. didactic approaches in the classroom, as possible pedagogical practices on Law and Movies (the use of films as a didactic strategy for undergraduate law courses). In recent years, to meet this student reality and to implement the National Curriculum Guidelines for the Undergraduate Law Course, it is necessary to confront the legal phenomenon in its dynamic performance with other cultural manifestations